The effects of robot's social praise on human responses in 2D game - Fadli, Nursabrina Suraya; Ghazali, Aimi Shazwani; Shamsul Bahrin, Muhammad Ikmal Hakim (Universitas Muhammadiyah Surakarta, 2022)
Human-Robot Interaction (HRI) is an interaction between humans and robots through verbal and/or non-verbal cues. Studies in the HRI field concern the psychological effect, especially reactance, experienced by humans in decision-making situations with robots. This study applied persuasive attempts to investigate the impact of social praise by a social robot on human psychological reactance in a decision-making situation. The robot socially expressed its recognition (an acknowledgement of the existence) and reassurance (the action of removing someone's doubts) towards humans in a game, namely